Assessment and prioritisation of low-carbon technology for the waste sector in Vietnam - Nguyen Van Thang; Le Ngoc Cau; Makoto Kato; Satoshi Sugimoto (Vietnam Journal of Science, Technology and Engineering, 2019)
This paper presents a multi-criteria assessment approach for the prioritisation of low-carbon technologies for the waste sector in order to enable the implementation of Vietnam’s nationally determined contributions (NDCs) in terms of the Paris Agreement. A four-step approach is developed for assessing and prioritising low-carbon technologies for the waste sector using this approach. A set of five criteria and indicators are defined for multi-criteria assessment. Based on mitigation options defined in the NDCs, a shortlist of 26 technological options are defined. The multi-criteria assessment and prioritisation is conducted based on the shortlist. The assessment results in eight prioritised low-carbon technologies. Of the eight technologies prioritised, semi-aerobic landfill, which is a low cost and relatively simpler technology than the other technologies evaluated and can contribute to greenhouse gas emission reduction, is given the highest priority. The technical, financial, and social and environmental feasibility of each of the technologies evaluated is presented.